(untitled) (Journal of Medical & Health Sciences Review, 2025)
Diabetes mellitus is a long-standing metabolic disease marked by persistently high blood glucose levels that interfere with the body’s normal wound-healing mechanisms. In diabetic individuals, the healing process is often delayed due to extended inflammation, reduced collagen production, poor angiogenesis, and a higher risk of infection, which can ultimately lead to chronic ulcers and even amputations. Topical antimicrobial agents such as Mupirocin 2%, Silver sulfadiazine 1%, and Fusidic acid 2% are widely used to aid healing, but there is a lack of comparative experimental evidence evaluating their effectiveness in diabetic wound conditions. The present study was designed to assess and compare the wound-healing potential of these three antimicrobial formulations in a dexamethasone-induced diabetic rat model, with particular attention to fasting blood glucose levels, wound contraction, granulation tissue formation, and epithelialization time. Adult albino male rats were divided into control and diabetic groups, each consisting of 4–6 animals. Diabetes was induced by administering dexamethasone (10 mg/kg, SC) for 10 consecutive days. A 6 mm full-thickness excision wound was created, and the respective topical treatments were applied daily for 10 days. Key parameters were monitored, including fasting glucose levels on days 1, 3, 7, and 10; wound contraction on days 5 and 11; granulation tissue weight; and epithelialization period. By day 10, diabetic rats exhibited fasting glucose levels exceeding 200 mg/dl. On day 11, wound contraction was greatest with Mupirocin (99%), followed by Silver sulfadiazine (85%), Fusidic acid (74%), and control (57%). Wet granulation weight was highest in the Mupirocin group. Epithelialization occurred in 10.5 days with Mupirocin, 14 days with Silver sulfadiazine, 11.75 days with Fusidic acid, and 19.25 days in the control group. These findings indicate that Mupirocin 2% offers superior wound-healing effects compared to the other treatments, supporting its use in managing diabetic wounds.